A High-performance Compact Photoacoustic Tomography System for In Vivo Small-animal Brain Imaging - Upputuri, Paul Kumar (J Vis Exp, 2017)
In vivo small-animal imaging has an important role to play in preclinical studies. Photoacoustic tomography (PAT) is an emerging hybrid imaging modality that shows great potential for both preclinical and clinical applications. Conventional optical parametric oscillator-based PAT (OPO-PAT) systems are bulky and expensive and cannot provide high-speed imaging. Recently, pulsed-laser diodes (PLDs) have been successfully demonstrated as an alternative excitation source for PAT. Pulsed-laser diode PAT (PLD-PAT) has been successfully demonstrated for high-speed imaging on photoacoustic phantoms and biological tissues. This work provides a visualized experimental protocol for in vivo brain imaging using PLD-PAT. The protocol includes the compact PLD-PAT system configuration and its description, animal preparation for brain imaging, and a typical experimental procedure for 2D cross-sectional rat brain imaging. The PLD-PAT system is compact and cost-effective and can provide high-speed, high-quality imaging. Brain images collected in vivo at various scan speeds are presented.